Rethinking Islam and Modernity Kajian Pemikiran Fathi Osman tentang Plurarisme dan HAM - Muslimin Muslimin; Muzammil Muzammil (Moderasi : Journal of Islamic Studies, 2025)
The intersection of religious tradition and modern values often generates tension, particularly regarding issues of pluralism and human rights. This study aims to explore the thought of Fathi Osman, a prominent Muslim scholar, in reconciling Islamic texts with the demands of modernity. Using a qualitative library research method with a descriptive-analytical approach, this research examines Osman’s key works, including Rethinking Islam and Modernity and The Children of Adam. The findings reveal that Osman proposes a fundamental methodological shift: distinguishing between the immutable divine text (nash) and dynamic human interpretation. Consequently, he argues that pluralism in Islam transcends passive tolerance, requiring legal institutionalization to guarantee equality. Regarding human rights, Osman deconstructs patriarchal interpretations of gender roles redefining qawwamun as functional rather than ontological and advocates for shifting from the classical dhimmi status to equal citizenship for non-Muslims. The research concludes that Islam possesses inherent compatibility with modernity. The primary barriers to implementation are not theological but rather socio-political oppression and intellectual stagnation. Osman’s framework offers a strategic roadmap for Muslims to abandon "ghetto-mindedness" and embrace their role as proactive world citizens